A framework to evaluate service user experience as a tool to achieve service excellence in Malaysian Local Governments - Umar, Muhammad Akilu; Kasim, Rozilah; Martin, David; Abubakar, Muhammad; Umar, Muhammad Bello; Ahmed, Tanko Husseini (JARDCS, 2018)
The quest to achieve Service excellence is a global phenomenon, it cut across various range of public services. Within the three tiers of the government, local governments are charged with the responsibility of taking care of the environment part of which is its cleanliness and collection of garbage. The contribution of this paper is highlighted in the methodological steps followed in research framework development. The main objective is to provide a blueprint for the development of research framework which guides the entire research process. The research involves both deductive and inductive approach. This implies that the paper dwelt on theoretical and conceptual framework since it is built based on existing body of knowledge and pilot study are applied in the paper to assist in developing a suitable research framework to evaluate service user experience as tool to achieve service excellence in Malaysian LG‟s. The framework provides a procedure for establishing critical areas for enhancing service delivery towards developing FM service user indicators